The growing role of web-based geospatial technology in disaster response and support - Kawasaki, Akiyuki; Berman, Merrick Lex; Guan, Wendy (Disasters, 2013)
This paper examines changes in disaster response and relief efforts and recent web‐based geospatial technological developments through an evaluation of the experiences of the Center for Geographic Analysis, Harvard University, of the Sichuan (2008) and Haiti (2010) earthquake responses. This paper outlines how conventional GIS (geographic information systems) disaster responses by governmental agencies and relief response organisations and the means for geospatial data‐sharing have been transformed into a more dynamic, more transparent, and decentralised form with a wide participation. It begins by reviewing briefly at historical changes in the employment of geospatial technologies in major devastating disasters, including the Sichuan and Haiti earthquakes (case studies for our geospatial portal project). It goes on to assess changes in the available dataset type and in geospatial disaster responders, as well as the impact of geospatial technological changes on disaster relief effort. Finally, the paper discusses lessons learned from recent responses and offers some thoughts for future development.